Strategi Pengelolaan Zakat, Infak, dan Shadaqah di Fakultas Ekonomi dan Bisnis UHAMKA - Tohirin Tohirin (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2020)
This study aims to find the ideal management model for zakat, infaq, and shadaqah (ZIS). The research object is the Laboratory of Social Entrepreneurship and Islamic Philanthropy (LKSFI), Faculty of Economics and Business, Prof. Muhammadiyah University. DR. Hamka (FEB-UHAMKA) Jakarta. This research uses a qualitative approach. Data Collection Techniques The technique used in collecting data in this study was in-depth interviews with several key informants, which consisted of: (1) LKSFI leaders, (2) LAZISMU-UHAMKA leaders, (3) ) Dean of FEB-UHAMKA, (4) LKSFI volunteers, (5) lecturers, (6) students, and (7) local communities, especially mustahiq and muzaki. As a support, observation and document analysis are used. The data analysis technique was carried out in three stages: data reduction, data presentation, and drawing conclusions. The final conclusion is that FEB-UHAMKA has an innovative strategy in managing zakat, infaq and shadaqah. Unlike ZIS gathering institutions in general, FEB-UHAMKA established an Islamic social entrepreneurship and philanthropy lab as a driving force then collaborated with LAZISMU-UHAMKA and Mini Bank in managing ZIS. The establishment of the lab has become a separate model that is relevant to the academic world so that it has received positive responses from various parties.